Supply Chain Management and Transport Logistics. - Liu, John J. (Taylor & Francis, 2011)
The enterprise-focused framework of supply chain, which an overwhelming majority of books on supply chain management (SCM) have adopted, falls short in explaining recent developments in the real world, especially the so-called Wal-Mart model, in which a 'factory' is a virtual logistics network of multiple international manufacturing firms. The book fills the gap and examines supply chain and transport logistics. The book also includes the development of a unified methodological framework which underpins all the characteristics of the interrelationship between supply chain management and logist.